Vidas Secas de Graciliano Ramos e Os Flagelados do Vento Leste de Manuel Lopes : um estudo do núcleo familiar a luz da metodologia comparatista - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This final paper, whose title is “Vidas Secas”, by Graciliano Ramos, and “Os Flagelados do Vento Leste”, by Manuel Lopes: a study about family nucleus in the view of comparative methodology, showing that both share similar themes, exploring contryside life, the drought, social injustices and the difficulties faced by disadvantaged populations. The study seeks to identify the particularities that stand out in each piece and to understand how literacy influences, especially the 30’s Brazilian romances, manifest in Cape Verdean literature and how the inspiration in Brazilian literature contributed to the affirmation Cape Verde’s cultural identity. Furthermore, we want to show the significance of Brazilian literary production in the construction of cultural and social awareness in Cape Verde, promoting reflection on the seek for an authentic literary expression, that dialogues with local issues, but also connects wider literary and social movements. The analysis intends, in this way, contributes to the understanding of interconnections between literatures from different regions and the way in which these interactions shape cultural and narrative identities. Both novels reveal the constant struggle against the drought and the different ways of resistance, adopted by the families that center the narrative. Were fundamental for this study, theoretical-critical texts by author such as: Alfredo Bosi, José L. Cabaço, Tania Carvalhal, Rita Chaves, Cremilda de Araújo and Jane Tutikian, and others.
Keywords: Seca; Literatura Comparada; Núcleo Familiar; Graciliano Ramos; Manuel Lopes; Drought; CNPQ::LINGUISTICA, LETRAS E ARTES